If *f *(*x*) = *x^*2 − 2*x *, show by completing the square that;

*f *(*x *− 1) = (*x *− 2)^2 − 1.

### 1 Answer | Add Yours

`f(x) = x^2-2x`

To get `f(x-1)` we should replace `x` by `(x-1)` .

`f(x-1) = (x-1)^2-2(x-1)`

`f(x-1) = x^2-2x+1-2x+2`

`f(x-1) = x^2-4x+3`

`x^2-4x`

`= x^2-4x+4-4`

`= (x^2-4x+4)-4`

`= (x-2)^2-4`

`f(x-1) = (x-2)^2-4+3`

`f(x-1) = (x-2)^2-1`

*So the required answer is obtained.*

`f(x-1) = (x-2)^2-1`

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes